15N Characterization of Landfill Nitrogen and its Application to Fingerprint Landfill-Leachate in Contaminated Groundwater and Surface water - Bustos, Andres Urrutia; Aravena, Ramon (Águas Subterrâneas, 2011)
A study was carried out to study the fate of ammonium in landfill-leachate contaminated groundwater and surface water. A characterization of the concentration and isotopic signature of ammonium in landfills was firstly done, and secondly a plume of contamination rich in ammonium was investigated to evaluate both the fate of the landfill ammonium concentration and its 15NH4 signature along the groundwater flow system and along the course of a creek, both impacted by the landfill leachate. The study showed that the isotopic signature of the landfill ammonium was conserved along the groundwater flowpath despite attenuation of ammonium along the flowpath, and therefore it can be used as a tool for fingerprinting landfill leachate contamination.